(untitled) (Czech Journal of Multidisciplinary Innovations, 2024)
Ahmad Donish always followed the example of his spiritual teachers who lived before him and left an immortal mark on history, and initiated his educational activities. At the same time, he encouraged his students and colleagues to express their opinions openly. Ahmad Donish embodied in himself the example of hardworking service of poets and statesmen of the distant past. The article discusses the factors that contributed to Ahmad Donish’s rise to the status of an enlightened scholar. It also extensively examines the life and scientific legacy of the thinker, as well as the insights of subsequent generations.